Postsynthetic deamidation of hemoglobin Providence (beta 82 Lys replaced by Asn, Asp) and its effect on oxygen transport. - Charache, S (1977)
Carriers of hemoglobin Providence have three types of beta chain in their hemolysates. The two abnormal chains have asparagine (Providence N, Prov N) or aspartic acid (Providence D) at position beta 82, instead of lysine. In vitro, only two beta chains are synthesized by reticulocytes of carriers, betaA and betaProv N. In vivo studies showed that the specific activity of Providence N was initially 10-fold higher than that of Providence D; the specific activities of the two labeled hemoglobins were approximately equal 5 wk after injection of isotope. Oxygen affinity of carriers' blood was somewhat increased, but they were not polycythemic. The affinity of the purified hemoglobins Providence was decreased. Addition of 2, 3 diphosphoglycerate had little effect on the affinity of either hemoglobin component, and addition of inositol hexaphosphate produced no change in the affinity of Providence D. These studies demonstrate that Providence N is deamidated to Providence D during the life span of the erythrocyte, and suggest this finding may represent only an easily observed prototype of posttranslational modification of proteins in general. Despite and abnormal P50 of the blood, oxygen transport is probably normal in carriers of the abnormal hemoglobins.